Study on Clinicopathological Features and Risk Factors of Patients with Multiple Primary Breast Cancers and Thyroid Disease - Jie Li; Yonghong Liu; Jian Jin; Qingfeng Shi; Yanting Ji; Bo Zhang; Pengfei Hu (Hindawi Limited, 2023)
Objective. To explore the clinicopathological features and risk factors of patients with multiple primary breast cancers and thyroid disease. Method. An analytic approach of the reviewing method was adopted to analyze the clinical data of 80 breast cancer patients who were admitted to our hospital from January 2020 to January 2022. They were divided into an observation group (breast cancer with thyroid lesions) and a control group (simple breast cancer) according to whether the clinical data were accompanied with thyroid lesions to compare the clinical characteristics, pathological types, staging characteristics, and molecular biological characteristics of the two groups and to research the risk factors of the two groups. Result. (1) In the comparison of clinical data, the number of people aged ≥60 in the observation group was higher than that in the control group, and there was significant difference between the groups in the menopausal status data (P<0.05). There was no statistical difference between the observation group and the control group in the comparison of clinical data of the body mass index, pregnancy frequency, labor frequency, and abortion history (P>0.05). (2) In the comparison of pathological type and staging data, there was no statistical difference in the comparison of data on the pathological type, histological grade, T staging, N staging, and TNM staging between the observation group and the control group (P>0.05). (3) In the comparison of data on molecular biology characteristics, there was a statistical difference in the nuclear proliferation antigen data between the observation group and the control group (P<0.05). There was no statistical difference in the comparison of data on the estrogen receptor, progesterone receptor, human epidermal growth factor receptor-2, and molecular typing between the observation group and the control group (P>0.05). (4) Logistic regression analysis showed that age, menopausal status, and nuclear proliferation antigen index were the high-risk inflammatory factors for combined thyroid lesions (P<0.05). Conclusion. For patients with simple breast cancer, age, menopausal status, and nuclear proliferation antigen index are risk factors for combined thyroid lesions. Therefore, clinical attention should be paid to the above factors in the process of clinical treatment, and early-risk screening should be performed to achieve the purpose of improving the prognosis to the greatest extent.